Aging for 35 days does not improve tenderness of strip loin steaks from heifers fed Zilmax - Ebarb, Sara M.; Phelps, Kelsey; Van Bibber-Krueger, Cadra L.; Drouillard, James S.; Gonzalez, John M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
As the world’s population continues to expand, demand for food animal products is also increasing; therefore, efficient production is vital. Implants and beta-adrenergic agonists such as Zilmax (Merck Animal Health, Summit, NJ) improve average daily gain and feed efficiency in feedlot cattle. Use of these growth technologies also increases hot carcass weight and muscle mass. Although use of implants and Zilmax increases efficiency of beef production, these products also negatively affect meat quality characteristics such as marbling and tenderness. Some research reports conclude that wet aging meat for extended periods of time can alleviate tenderness issues caused by exogenous growth promotants. The objective of this experiment was to examine the effects of implants and Zilmax on meat tenderness across five aging periods and to evaluate moisture retention during the cooking process.
Keywords: Beef; Zilmax; Tenderness; Weight gain